Study of laparoscopic cholecystectomy in gallstones induced pancreatitis - Bisht, Abhinav; Rehmani, Babar (International Surgery Journal, 2018)
Background: Many general surgeons still harbor a notion that laparoscopic cholecystectomy in patients with acute gallstone induced pancreatitis has a higher morbidity. The timing of cholecystectomy in these patients is a matter of debate. Aim of the study was to assess the degree of difficulty, the timing of laparoscopic cholecystectomy (LC), and the complications of surgery in patients of gall stone pancreatitis subjected to laparoscopic cholecystectomy. Methods: 69 patients were diagnosed with gall stone induced pancreatitis over a period of 12 months and 46 underwent laparoscopic cholecystectomy. After an acute attack of pancreatitis the procedure was performed on index admission or was delayed for an interval of 3 to 4 weeks, thereby dividing the study sample into two on the basis of timing of surgery. The severity of pancreatitis was graded according to the Revised Atlanta criteria. Results: All the patients who underwent laparoscopic cholecystectomy had either mild or moderate severity of pancreatitis. Comparing the two groups with regard to timing of cholecystectomy, no statistically signiﬁcant difference was noted in operating time, difficulty in surgery, conversion rate to open procedure or post-operative stay. Conclusions: Laparoscopic cholecystectomy in patients with gallstone induced pancreatitis does not attribute any additional risk and does not have increased morbidity nor is there any increase risk of conversion.